Awe, curiosity, and multicultural experience. Issue 3 (16th August 2022) - Zhang, Jia Wei; Howell, Ryan T.; Januchowski, Joseph A.; Ramis, Tamilselvan; Mello, Zena; Monroy, Maria
Abstract: Introduction: Despite broad consensus about multicultural experience's benefits, there is a lack of research on the antecedents to multicultural experiences. Research has indicated that awe shifts attention away from the self toward larger entities, which could include elements of other cultures. Methods: Four studies ( N  = 2915) tested whether trait, daily, and induced awe promoted multicultural experience. Results: Studies 1–2 (adolescents, young, middle, and older adults) showed that trait awe predicted greater multicultural identity and experience independent of other positive emotions and openness. Study 3 (students & adults in U.S. & Malaysia) demonstrated that daily awe predicted more daily multicultural experience independent of yesterday's multicultural experience. These results were explained by trait and daily curiosity. Study 4 (adults) found that induction of awe increased state multicultural identity and experience via state curious emotions and then state curious personality. Conclusion: We found that experiencing more awe can be a tool for enhancing the multicultural experience. The discussion focuses on the implications for future research on awe and multicultural experiences.